The Relationship between Perceptions and Family Behavior in Preventing Dengue Hemorrhagic Fever - Adhani, Nida Rahmatul; Arneliwati, Arneliwati; Tampubolon, Masrina Munawarah (CV. Rayyan Dwi Bharata, 2023)
Introduction: Dengue hemorrhagic fever (DHF) is an infectious disease that is experienced by many tropical countries, including Indonesia. Prevention of dengue fever relies heavily on the active role of the community, especially families, in controlling the population of the Aedes aegypti mosquito as the vector of the disease. This study aims to examine the relationship between perceptions and family behavior in efforts to prevent dengue fever. Method: The method in this research uses a descriptive correlation design with a sample size of 98 respondents using the Purpose Sampling technique. The measuring instrument used is a questionnaire and the analysis used is bivariate analysis using the chi square test. Results: The majority of respondents were in late adulthood (36-45 years) (35.7%), the majority worked as entrepreneurs (50%), the majority had graduated from high school/vocational school (68.7%) and the majority owned private homes (72.4% ). The picture of family perception is negative perception with a total of 58.2%. The description of family behavior was adequate as much as 57.1%. The results of the chi-square statistical test obtained p-value=0.016 (p0.05). Conclusion: There is a relationship between perceptions and family behavior in preventing dengue hemorrhagic fever (DHF).